The mediating role of work engagement between job crafting and job performance among national secondary school teachers - Bhargkavi Pari; Alia Azalea (Penerbit Universiti Kebangsaan Malaysia, 2019)
Employees who are able to craft their working atmosphere are expected to be more engaged with the tasks in their job, which eventually will boost their job performance. Based on Job Demands-Resources theory, this study hypothesised that work engagement mediates the relationship between secondary school teacher’s job crafting and job performance. A quantitative design using questionnaires consisted of Job Crafting Scale, Utrecht Work Engagement Scale, Task-Based Job Performance Scale and Organizational Citizenship Measure. Four hundred secondary school teachers in the Kedah state located in the northern region of Malaysia were recruited for this study. Using PROCESS, a technique by Hayes (2015) this study was able to support its hypothesis. This study has contributed to the literature of job crafting in the Malaysian context. The findings of this study can be used by educational policymakers and school management to promote teacher’s job crafting behaviour as it uplifts teachers’ work engagement and eventually their job performance.